2022
DOI: 10.1016/j.ijppaw.2022.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary monitoring of gastrointestinal parasites in European bison, Bison bonasus designated for translocation: Comparison of two coprological methods

Abstract: It is important to monitor the level of parasitic loads in herds of European bison and to identify threats early enough to prevent their spread to other populations or species. The aim of the present study was to compare the detection sensitivity of two fecal flotation techniques, viz. the modified Willis method (WM) with centrifugation and modified McMaster flotation technique (MM), in the diagnostics of gastrointestinal parasites of European bison before the translocation of animals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, local parasite populations seem to have drug-resistant traits, which highlights the need for further research. It is reasonable to introduce preventive measures such as enclosure rotations and differentiated deworming protocols, and every newly imported animal should be treated as being potentially infected with drug-resistant parasites ( Conder and Campbell, 1995 ; Gałązka et al, 2022 ). Drug resistance may develop for various reasons in captive non-domestic animals, such as inaccurate determination of body weight, which results in incorrect anthelmintic drug doses; in addition, individual drug administration and ensuring complete dosage intake can also be problematic, and there may be limited possibilities for enclosure rotation ( Conder and Campbell, 1995 ; Coles et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, local parasite populations seem to have drug-resistant traits, which highlights the need for further research. It is reasonable to introduce preventive measures such as enclosure rotations and differentiated deworming protocols, and every newly imported animal should be treated as being potentially infected with drug-resistant parasites ( Conder and Campbell, 1995 ; Gałązka et al, 2022 ). Drug resistance may develop for various reasons in captive non-domestic animals, such as inaccurate determination of body weight, which results in incorrect anthelmintic drug doses; in addition, individual drug administration and ensuring complete dosage intake can also be problematic, and there may be limited possibilities for enclosure rotation ( Conder and Campbell, 1995 ; Coles et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, WM and SM represent the test tube and cover slip approach to faecal egg counting in contrast to methods representing the counting chamber approach, such as MM (12). On the other hand, WM is a qualitative method, whereas SM and MM are quantitative coprological techniques (7,17). Gałązka et al (7) reported that WM yielded a higher prevalence of eggs and oocysts in European bisonderived samples than MM.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, WM is a qualitative method, whereas SM and MM are quantitative coprological techniques (7,17). Gałązka et al (7) reported that WM yielded a higher prevalence of eggs and oocysts in European bisonderived samples than MM. The statistical analysis of the results of this study revealed that WM offers an advantage in the detection of eggs of Trichostrongylidae and Nematodirus, whereas SM does in the detection of smaller coccidia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…European bison (Bison bonasus L.) is a species for which health monitoring is essential in conservation activities [5][6][7][8] . Due to the low genetic variability of the European bison, even large free-living herds struggle with health problems, and sometimes it is necessary to implement restrictive measures to eliminate sick individuals (e.g.…”
mentioning
confidence: 99%